Археологические разведки побережья Хаджибейского лимана - Бербек, Ю.Г.; Денисюк, В.Л. (Материалы по археологии Северного Причерноморья, 2009)
In this article a location already of the known monuments of epoch of bronze is specified on the banks of Khadzhibeyskogo of estuary, and also new locations, becomings known as a result of archaeological prospectings of the last years, are entered in a scientific turn. In addition, in the article a hypothesis is pulled out about existence in the epoch of bronze of ferriage through an estuary.